2017
DOI: 10.1080/02713683.2017.1349154
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Laser Indirect Ophthalmoscope: For the Induction of Choroidal Neovascularization in a Mouse Model

Abstract: The mobile laser indirect ophthalmoscope can serve as a feasible and a reliable alternative method for the CNV induction in a mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Next, we induced CNV in the eye by laser treatment 6 weeks after injection of AAV-Cpf1- Vegfa or - Hif1a and measured the area of CNV 25 1 week later (Fig. 3a ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we induced CNV in the eye by laser treatment 6 weeks after injection of AAV-Cpf1- Vegfa or - Hif1a and measured the area of CNV 25 1 week later (Fig. 3a ).…”
Section: Resultsmentioning
confidence: 99%
“…The current efficacious treatments for CNV are mostly based on anti-VEGF agents, yet, suboptimal response, slow loss of efficacy, and long term concerns regarding the continuity of the neurodegenerative process restricted their full success [1,2,23]. Using the laser-induced CNV mouse model, we previously demonstrated that APC treatment reduced CNV to a similar extent as bevacizumab [7,13].…”
Section: Discussionmentioning
confidence: 99%
“…All animal experiments were performed according to the Association for Research in Vision and Ophthalmology (ARVO) statement's guidelines for the Use of Animals in Ophthalmic and Visual Research and the approval of the Institutional Animal Care and Use Committee at Rabin Medical Center. CNV was induced based on Weinberger et al [13] as previously described [7]. Briefly, diode laser indirect ophthalmoscope (Iris Medical Oculight SLX System©, Iridex, Mountain View, CA, USA) was used with a laser power of 350 mW for a duration of 100 msec and a condensing lens of 90 diopters.…”
Section: In Vivo Laser-induced Cnv Animal Modelmentioning
confidence: 99%
“…CNV was performed as previously described by Weinberger et al [65] Briefly, diode laser indirect ophthalmoscope (Iris Medical Oculight SLX System©, Iridex, Mountain View, CA, USA) was used with laser power of 350 mW for duration of 100 msec, and a condensing lens of 90 diopters. Three laser applications were applied on the right eye, at a distance of 1 to 2 optic disc diameters around the optic nerve.…”
Section: Methodsmentioning
confidence: 99%